Nuevos genes de resistencia a herbicidas - WRIGHT, Terry; LIRA, Justin M; LIN, Gaofeng; MERLO, Donald; JAYAKUMAR, Pon Samuel; WALSH, Terence Anthony (2017)
Un método de cultivo de plantas que comprende una molécula de ácido nucleico que codifica una proteína que hibrida en condiciones rigurosas con el complemento completo de una secuencia seleccionada del grupo que consiste en SEQ ID NO: 1, SEQ ID NO: 3 y SEQ ID NO: 5 en una zona, comprendiendo dicho método: aplicar uno o más herbicidas de ariloxialcanoato a dicha zona para controlar las malas hierbas, incluyendo la aplicación preplantas de dicho herbicida a dicha zona antes de sembrar dicha zona con semillas para dichas plantas. The subject invention provides novel plants that are not only resistant to 2,4-D, but also to pyridyloxyacetate herbicides. Heretofore, there was no expectation or suggestion that a plant with both of these advantageous properties could be produced by the introduction of a single gene. The subject invention also includes plants that produce one or more enzymes of the subject invention "stacked" together with one or more other herbicide resistance genes. The subject invention enables novel combinations of herbicides to be used in new ways. Furthermore, the subject invention provides novel methods of preventing the development of, and controlling, strains of weeds that are resistant to one or more herbicides such as glyphosate. The preferred enzyme and gene for use according to the subject invention are referred to herein as AAD-12 (AryloxyAlkanoate Dioxygenase). This highly novel discovery is the basis of significant herbicide tolerant crop trait and selectable marker opportunities.